Melatonin improves rate of monospermic fertilization and early embryo development in a bovine IVF system. - Juan Carlos Gutiérrez-Añez (Public Library of Science (PLoS), 2021)
The developmental competence of male and female gametes is frequently reduced under in vitro conditions, mainly due to oxidative stress during handling. The amino-acid derived hormone melatonin has emerged as a potent non-enzymatic antioxidant in many biological systems. The goal of the present study was to evaluate the effects of melatonin on post-thaw sperm quality, fertilizing ability, and embryo development and competence in vitro after in vitro fertilization. Frozen-thawed bovine spermatozoa were incubated either in the presence of 10-11 M melatonin (MT), or its solvent (ethanol; Sham-Control), or plain Tyrode's Albumin Lactate Pyruvate medium (TALP, Control). Computer-Assisted Sperm Analysis (CASA) and flow cytometry data after 30 min, 120 min, and 180 min incubation did not reveal any significant effects of melatonin on average motility parameters, sperm subpopulation structure as determined by hierarchical cluster, or on the percentage of viable, acrosome intact sperm, or viable sperm with active mitochondria. Nevertheless, in vitro matured cumulus-oocyte-complexes fertilized with spermatozoa which had been preincubated with 10-11 M melatonin (MT-Sperm) showed higher (P < 0.01) rates of monospermic fertilization, reduced (P < 0.05) polyspermy and enhanced (P < 0.05) embryo development compared to the Control group. Moreover, the relative abundance of MAPK13 in the in vitro-derived blastocysts was greater (P < 0.05) than observed in the Control group. In conclusion, adding melatonin to the sperm-preparation protocol for bovine IVF improved proper fertilization and enhanced embryonic development and competence in vitro.